PULMONARY SCREENING IN RHEUMATOID ARTHRITIS PATIENTS AT A TERTIARY HOSPITAL: AN OBSERVATIONAL STUDY FROM CENTRAL INDIA - Bugalia, Praveen Kumar; Agarwal, Raj Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Given that rheumatoid arthritis (RA) is an inflammatory systemic illness and that lung disease affects RA morbidity and mortality, it has been advised that asymptomatic RA patients be screened for pulmonary involvement. Aims & objectives: In the current investigation, rheumatoid arthritis patients at a tertiary hospital underwent lung screening as part of an observational study. Material and Methods: Patients who met the ACR EULAR (2010) criteria for rheumatoid arthritis and were older than 21 years old received pulmonary screening using physiological (a pulmonary function test) and radiographic methods in the current investigation, which was cross-sectional and observational in nature (chest X-ray, HRCT chest). Results: 128 rheumatoid arthritis patients were assessed in the current study. 53.31 11.06 years was the average age. There were fewer male patients (26.6%) than female patients (73.4 percent ). The majority of patients (60.9 percent) had RA illness for more than 10 years, had a normal BMI (45.3 percent), and did not smoke (59.4 percent ). 14.1% of people smoked regularly. Cough (43.8 percent), shortness of breath (17.2%), sputum (14.1 percent), and wheeze were the most prevalent symptoms identified (7.8 percent ). The majority of patients’ X-ray chest findings (81.3%) were normal, followed by b/l lower zone haziness (14.1%) and significant pulmonary vasculature (4.7 percent ).The majority of patients (73.4%) on HRCT exhibited normal findings, followed by ground glass pat (both lower lobes) (17.2%), sub pelural reticulations (10.9%), pleural thickening (3.1%), and pulmonary vascular prominence (3.1 percent ). The majority of patients (65.6%) had normal results from pulmonary function tests, followed by patients who had restrictive changes (17.2%), obstructive changes (10.9%), and non-cooperative patients (6.3%). Conclusion: Patients with rheumatoid arthritis who undergo pulmonary screening benefit from early diagnosis, treatment, and monitoring that lowers morbidity and death. Keywords: Pulmonary screening, rheumatoid arthritis, chest X-ray, HRCT chest